A Robust Métier-Based Approach to Classifying Fishing Practices Within Commercial Fisheries - Parsa, Mahdi; Emery, Timothy J.; Williams, Ashley J.; Nicol, Simon (Frontiers in Marine Science, 2020)
Developing a typology of heterogeneous fishing practices through the use of métier analysis is a useful step in understanding the dynamics of fishing fleets and enabling effective implementation of management outcomes. We develop a non-hierarchical clustering method framework to quantitatively categorize categorise individual fishing events to a particular métier based on corresponding catch composition, gear configuration and spatial and temporal references. Our method clustering framework has several innovations over predecessors including: i) introducing alternative methods for encoding and transforming fisheries data;new methods of encoding and transforming fisheries data; (ii) variable (feature) selection methods; (iii) complementary metrics and methods for internal métier validation; and (iv) use of a network science method to model and analyse analyse fishing practices. To demonstrate applicability, we apply this framework to the strengths of this method, we apply it to the Australian Eastern Tuna and Billfish Fishery (ETBF), an Australiana multispecies pelagic longline fishery with a diversity of fishing practices. We identified a total of seven stable métiers within the ETBF. While each métier was, characterised characterised by a single predominant target species, and they were differentiated more by seasonal and temporal references (e.g. time of set, month, latitude) than gear configuration (e.g. hooks per basket) or target species. By collapsing a large amount of high-dimensional operational data into a relatively uniform and limited number of components, decision-makers can more easily evaluate the likely consequences of management and design policies that target particular homogenous fishing practices. a particular métier.